Old Words, New Meanings: A Study of Trends in Science Librarian Job Ads. - Brenna K. H. Bychowski; Mia C. Costa; Jessamyn Sudhakaran (Issues in Science and Technology Librarianship)
Job ads are supposed to provide careful descriptions of the positions being advertised. Based on this premise, an analysis of job ads over time should reveal emerging trends and changes in a profession. The existing literature on science librarianship emphasizes that there are fluctuations in the demand for subject expertise and technology skills at different periods of time. After gathering job ads from the beginning and end of a ten-year period, a close reading of the ads revealed surprisingly few changes in the requirements for science librarian positions. This suggests that what employers are looking for has not changed in spite of the changes in the profession. This analysis also points to a set of core qualities in the profession, though what the qualities mean could have changed over time. This study explores the data gathered from the collected ads and offers some explanations for the results. [ABSTRACT FROM AUTHOR]